REPORTAGES ABOUT THE END OF THE WORLDS. OLD GALICIA AND BIAŁOSTOCCZYZNA ACCORDING MARTIN POLLACK AND WŁODZIMIERZ PAWLUCZUK - Kopeć, Zbigniew (Porównania, 2014)
The article is an attempt of showing how two contemporary works which refer to the form of reportage depict the late 19th century experience of the multinational Austro-Hungarian Empire (Pollack). On the other hand, it shows how this loss is experienced by regular people on the eastern edges of the Romanov empire. Pollack takes a look at the inhabitants of former Galicia from a multicultural and civilisational development perspective. Pawluczuk describes the group formed around the prophet Ilja from the perspective of religious and anthropological studies. Both authors show worlds which had to go away, yet Pawluczuk sees it as a reservoir of spiritual values.